Pengaruh Motivasi Kerja Dan Soft Skill Terhadap Profesionalitas Guru Di SMAK ST. Gabriel Maumere - Elisabeth Kristanti Nona Novi; Paulus Juru; Walter Obon (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aimed to: (1) Know the description of teacher professionalism, work motivation, and soft skill, (2) analyze the influence of word motivation and soft skill ont teacher professionalism both partially and simultaneously. The populations in thus study were 50 teachers of SMAK St.Gabriel Maumere. Due to limited populations, this research was conducted through a census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistic, namely multiple linear regressions. Hypotthesis testing was done through the F test and t test. The results of the descriptive analysis showed that the variables of teacher professipnalism, work motivation and soft skill were categorized as very good. The results of the t-test statistic showed that partially the variables of word motivation and soft skilol hand a positive and significant effect on teachers’ professionalism. The statistical result of the F test showed that simultaneously the variables of work motivation and soft skil had a significant effect on teacher professionalism.The statistical results of the F test showed that simultaneously the variables of work motivation and soft skills hand a significant effect on teacher professionalism, The results of the determination analysis showed that the two independent variables in this research were able to explain the variation of the teacher professionalism enhancement at SMA St.Gabriel Maumere by 82.00%